Corruption - a deviation or an inherent part of human society? Some legal considerations: (conference proceedings, June, 8th 2016, Ljubljana, Slovenia) / 5th Traditional Law Conference of the University of Ljubljana, Faculty of Law, Özyegin U (University of Maribor Press, 2017)
Corruption is a dishonest or unethical conduct by a person (also company, state…) entrusted with a position of authority, with the intention to acquire certain benefits or advantages. Nowadays, corruption is present in all states and societies, and could be widespread in all legal and human relations. Corruption is mostly associated with embezzlement, bribery, coercion, extortion, blackmail… Therefore, the corruption is mostly of illegal nature. International and national anti-corruption initiatives and actions pay special attention to the fields where the impact of corruption affects the most vulnerable groups of people. On the international level the most active role is played by Transparency International, an international organisation fighting against corruption.